Autoimmune Lymphoproliferative Syndrome (ALPS) Disease and ALPS Phenotype: Are They Two Distinct Entities?. Issue 3 (22nd March 2023) - Palmisani, Elena; Miano, Maurizio; Grossi, Alice; Lanciotti, Marina; Lupia, Michela; Terranova, Paola; Ceccherini, Isabella; Montanari, Eugenia; Calvillo, Michaela; Pierri, Filomena; Micalizzi, Concetta; Maggiore, Rosario; et al.
Abstract : Autoimmune lymphoproliferative syndrome (ALPS) is an inherited disorder of lymphocyte homeostasis classically due to mutation of FAS, FASL, and CASP10 genes (ALPS-FAS/CASP10). Despite recent progress, about one-third of ALPS patients does not carry classical mutations and still remains gene orphan (ALPS-U, undetermined genetic defects). The aims of the present study were to compare the clinical and immunological features of ALPS-FAS/CASP10 versus those of ALPS-U affected subjects and to deepen the genetic characteristics of this latter group. Demographical, anamnestic, biochemical data were retrieved from medical record of 46 ALPS subjects. An enlarged panel of genes (next-generation sequencing) was applied to the ALPS-U group. ALPS-U subjects showed a more complex phenotype if compared to ALPS-FAS/CASP10 group, characterized by multiorgan involvement ( P = 0.001) and positivity of autoimmune markers ( P = 0.02). Multilineage cytopenia was present in both groups without differences with the exception of lymphocytopenia and autoimmune neutropenia that were more frequent in ALPS-U than in the ALPS-FAS/CASP10 group ( P = 0.01 and P = 0.04). First- and second-line treatments were able to control the symptoms in 100% of the ALPS-FAS/CASP10 patients, while 63% of ALPS-U needed >2 lines of treatment and remission in some cases was obtained only after target therapy. In the ALPS-U group, we found in 14 of 28 (50%) patients 19 variants; of these, 4 of 19 (21%) were known as pathogenic and 8 of 19 (42%) as likely pathogenic. A characteristic flow cytometry panel including CD3CD4-CD8-+TCRαβ+, CD3+CD25+/CD3HLADR+, TCR αβ+ B220+, and CD19+CD27+ identified the ALPS-FAS/CASP10 group. ALPS-U seems to represent a distinct entity from ALPS-FAS/CASP10; this is relevant for management and tailored treatments whenever available.